Implikasi Klinis Axis Usus-Paru dalam Kemoterapi Sistemik untuk Kanker Paru-paru: Tinjauan Pustaka - Agatha, Indry; Kurnia, Widiya Hari; Machfud, Mirna Nastiti Louqi; Pangestika, Stella; Hidayatullah, Candra Muhammad Yusuf; Simanjuntak, Arya Marganda (PT Kalbe Farma Tbk., 2026)
Lung cancer incidence continues to increase globally, with an estimated mortality rate of 18% worldwide. Current management strategies focus on early screening, early treatment, and palliative care. However, more fundamental approaches are needed to improve treatment outcomes. The gut-lung axis has emerged as an important factor in lung cancer pathophysiology, as it plays a role in pulmonary immune defense and is influenced by changes in gut and lung microbiota. Alterations in microbial composition have been observed in lung cancer patients and may contribute to disease progression. Systemic chemotherapy, while targeting cancer cells, also exerts systemic effects that may disrupt gut and lung microbiota, leading to dysbiosis. These changes may influence treatment response, immune modulation, and clinical outcomes in lung cancer patients. This narrative review explores the role of the gut-lung axis in lung cancer and examines the impact of systemic chemotherapy on gut and lung microbiota. Understanding the interaction between chemotherapy and the gut-lung axis may provide insight into potential adjuvant strategies to improve treatment effectiveness and patient quality of life.